CONSIDERATIONS ON THE USE OF GRAMMATICAL FORMS IN THE KARLUK DIALECTS OF THE SAMARKAND REGION - Tillabayeva Zilola Rakhmatillayevna (Western European Studies, 2025)
This article focuses on information about the origin of the karluk language and dialect. Opinions were expressed about the dialects of the karluk region of Samarkand region and the agreements in the Uzbek literary language, their interchangeability. Conjunctions used in dialects and their meeting forms in the language of ancient written monuments are discussed
Keywords: karluk dialects of the Samarkand region; ancient written monuments